Computed Tomography-Defined Sarcopenia in Outcomes of Patients with Unresectable Hepatocellular Carcinoma Undergoing Radioembolization: Assessment with Total Abdominal, Psoas, and Paraspinal Muscles - Chih-Horng Wu; Ming-Chih Ho; Chien-Hung Chen; Ja-Der Liang; Kai-Wen Huang; Mei-Fang Cheng; Chih-Kai Chang; Chia-Hung Chang; Po-Chin Liang (Liver Cancer, 2023)
Introduction: Sarcopenia is an adverse prognostic factor in patients with liver cirrhosis and hepatocellular carcinoma (HCC). Image-based sarcopenia assessment allows a standardized method to assess abdominal skeletal muscle. However, which is an index muscle for sarcopenia remains unclear. Therefore, we investigated whether sarcopenia defined according to different muscle groups with computed tomography (CT) scans can predict the prognosis of HCC after radioembolization. Methods: In this retrospective study, we analyzed patients who underwent radioembolization for unresectable HCC between January 2010 and December 2019. Before treatment, the total abdominal muscle (TAM), psoas muscle (PM), and paraspinal muscle (PS) areas were evaluated using a single CT slice at the third lumbar vertebra. In previous studies, sarcopenia was determined using the TAM, PM, and PS after stratifying by sex. Finally, we investigated each muscle-defined sarcopenia to decide whether or not it can serve as a prognostic factor for overall survival (OS). Results: We included 92 patients (74 men and 18 women). TAM, PM, and PS areas were significantly higher in the men than in the women (all p < 0.05). The patients with sarcopenia defined using PM, but not TAM and PS, exhibited significantly poorer OS than those without sarcopenia (median 15.3 vs. 23.8 months, p = 0.034, 0.821, and 0.341, respectively). After adjustment for clinical variables, such as body mass index, liver function, alpha-fetoprotein level, clinical staging, treatment response, and posttreatment curative therapy, PM-defined sarcopenia (hazard ratio: 1.899, 95% confidence interval: 1.087–3.315) remained an independent predictor for the poor OS. Conclusion: CT-assessed sarcopenia defined using PM was an independent prognostic factor for the poorer prognosis of unresectable HCC after radioembolization.